Предмет: Алгебра,
автор: дамика1
упростите выражение и найдите его значение х(х+2)(х-2)-(х-3)(х^2+3х+9) при х=1/2
Ответы
Автор ответа:
0
x (x^2 - 4) - (x^3 - 27) =
= x^3 - 4x - x^3 + 27 =
= - 4x + 27
при x= 1/2
- 4*1/2 + 27 = - 2 + 27 = 25
= x^3 - 4x - x^3 + 27 =
= - 4x + 27
при x= 1/2
- 4*1/2 + 27 = - 2 + 27 = 25
Автор ответа:
0
Похожие вопросы
Предмет: Литература,
автор: divan33
Предмет: Қазақ тiлi,
автор: 1199292
Предмет: Английский язык,
автор: aziztadjimetov
Предмет: Информатика,
автор: DashaSavchenko
Предмет: Математика,
автор: ПоЛиНоЧкО40